Comparison of the periodic slab approach with the finite cluster description of metal–organic interfaces at the example of PTCDA on Ag(110). Issue 14 (5th February 2018) - Banerjee, Jaita; Behnle, Stefan; Galbraith, Martin C. E.; Settels, Volker; Engels, Bernd; Tonner, Ralf; Fink, Reinhold F.
Abstract : We present a comparative study of metal–organic interface properties obtained from dispersion corrected density functional theory calculations based on two different approaches: the periodic slab‐supercell technique and cluster models with 32–290 Ag atoms. Fermi smearing and fixing of cluster borders are required to make the cluster calculation feasible and realistic. The considered adsorption structure and energy of a PTCDA molecule on the Ag(110) surface is not well reproduced with clusters containing only two metallic layers. However, all clusters with four layers of silver atoms and sufficient lateral extension reproduce the adsorbate structure within 0.04 Å with respect to the slab‐supercell structure and provide adsorption energies of ( − 4.45 ± 0.08 eV) consistent with the slab result of −4.47 eV. Thus, metal–organic adsorbate systems can be realistically represented by properly defined cluster models. © 2018 Wiley Periodicals, Inc. Abstract : Cluster approaches combined with modern Quantum Chemistry methods provide reliable structures for metal–organic interfaces.